ESG VS Kinerja Perusahaan, Uji Empiris Perusahaan LQ45 - Siti Rahmi Nurannisa; Bandi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to identify the effect of Environmental, Social, and Corporate Governance (ESG) disclosure on the financial performance of companies in Indonesia, using Return on Assets (ROA) and Tobin's Q as indicators. Through panel data analysis of companies listed on the Indonesia Stock Exchange during the period 2017-2021, this study find that ESG scores have a significant positive effect on company ROA, but have no significant effect on Tobin's Q. These results prove that ESG disclosures can provide relevant information about a firm's financial performance, with ROA as a more responsive indicator to ESG factors. The implication of this study is that it is important for firms to improve their ESG disclosures to gain investor confidence and improve their financial performance.